Examining pre-service elementary mathematics teachers’ views regarding critical thinking and doing mathematical proof - Kiliçaslan, Elif Akşan; İskenderoğlu, Tuba Aydoğdu (JRAMathEdu (Journal of Research and Advances in Mathematics Education), 2023)
Like in proving, teachers have an important role in critical thinking because critical thinking is not an innately given skill, rather, it is acquired later in life. However, at this point, educators have a lot of responsibilities because if the individual can transfer critical thinking to his life at school age, he can live his life more meaningfully, be inquisitive and find solutions to problems after school. For this reason, the opinions of teachers and hence prospective teachers concerning both critical thinking and doing proof are important. In this study, survey and correlational research methods were used together since it was intended to explore the views of pre-service elementary mathematics teachers regarding critical thinking and doing mathematic proof and to understand whether these two correlates. The study was carried out on 158 pre-service elementary mathematics teachers enrolled in a state university in the Eastern Black Sea Region of Turkey. According to the results, the pre-service teachers in this study have a low level of critical thinking disposition. service teachers depending on the grade level at which they were studying. When the participating pre-service teachers’ opinions on mathematical proof were examined, it was noticed that mental process was the highest while self-confidence was the lowest.